La Défense / Zone B (1953-91): Light and Shadows of the French Welfare State - Pierre Chabard (Footprint)
Planned as early as 1958 by the Etablissement Public d’Aménagement de La Défense (EPAD, the first such agency in France), the business district of La Défense is a typical urban result of the French version of the welfare state: centralism, modernism, alliance between public and private elites. But with its vertical skyline, this district – called Zone A – constitutes only a small part of the operational sector of the EPAD; the other part, Zone B, coincides with the northern part of the city of Nanterre.